2019
DOI: 10.1101/751008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topological Data Analysis reveals robust alterations in the whole-brain and frontal lobe functional connectomes in Attention-Deficit/Hyperactivity Disorder

Abstract: AbstractThe functional organization of the brain network (connectome) has been widely studied as a graph; however, methodological issues may affect the results, such as the brain parcellation scheme or the selection of a proper threshold value. Instead of exploring the brain in terms of a static connectivity threshold, this work explores its algebraic topology as a function of the filtration value (i.e., the connectivity threshold), a process termed the Rips filtration in Topol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…TDA models the connectome as a topological space and characterizes its interaction patterns as geometric features, allowing it to simplify complex structures at different scales (Giusti et al, 2016; Santos et al, 2019; Centeno et al, 2021). In particular, TDA applied to functional connectomes is not affected by the potential biases of connectivity thresholding nor brain segmentation (Lee et al, 2012; Gracia-Tabuenca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…TDA models the connectome as a topological space and characterizes its interaction patterns as geometric features, allowing it to simplify complex structures at different scales (Giusti et al, 2016; Santos et al, 2019; Centeno et al, 2021). In particular, TDA applied to functional connectomes is not affected by the potential biases of connectivity thresholding nor brain segmentation (Lee et al, 2012; Gracia-Tabuenca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similar topological summary statistics have been described in analyzing brain connectomes of individuals with ADHD using 0D Vietoris-Rips complex persistent homology features 12 . Likewise, we also focus our analysis on 0D features; however, we generate our topological features using cubical complexes.…”
Section: Persistent Homology Backgroundmentioning
confidence: 80%
“…We use the features Carlsson Coordinates (CC), Persistent Entropy (PE) and the kernel feature of Reininghaus et al (2015). Additionally, we investigate the 0-dimensional features Area Under the Curve (AUC) Gracia-Tabuenca et al (2019) and Integrated Persistence Feature (IPF) Kuang et al (2019a), as both have shown to provide good differentiations when applied to attention-deficit/hyperactivity disorder (ADHD) and Alzheimer's disease, respectively. We show in Table D.8 the results on the fMRI (schizophrenia) dataset and on the scalp EEG (epilepsy) data; we present in Table D.9 the results in dimension 0 for both the scalp EEG and intracranial iEEG datasets, when using the alternative approach discussed in Sec.…”
Section: D3 0-dimensional Featuresmentioning
confidence: 99%